2013
DOI: 10.1007/s11103-013-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide annotation of genes and noncoding RNAs of foxtail millet in response to simulated drought stress by deep sequencing

Abstract: Drought is a major abiotic stress that affects plant growth, production, and survival. Plants have evolved sophisticated and highly complex reactions to drought stress, including large-scale transcriptome reconfiguration. Foxtail millet (Setaria italica) is a member of the Poaceae family. Because of its outstanding tolerance to drought stress foxtail millet has the potential to become a new model organism. To enrich our knowledge of the processes that contribute to drought resistance, we have used a deep seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 105 publications
1
105
4
Order By: Relevance
“…Previous studies have found much larger numbers of differentially expressed sRNAs under abiotic stresses in Brachypodium and foxtail millet (Qi et al, 2013). Our experiments detected a much smaller number of stress-modulated sRNA loci.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Mcontrasting
confidence: 43%
See 1 more Smart Citation
“…Previous studies have found much larger numbers of differentially expressed sRNAs under abiotic stresses in Brachypodium and foxtail millet (Qi et al, 2013). Our experiments detected a much smaller number of stress-modulated sRNA loci.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Mcontrasting
confidence: 43%
“…Our experiments detected a much smaller number of stress-modulated sRNA loci. This could be due to the different stress protocols: the previous studies applied more severe stress conditions, such as polyethylene glycol-simulated drought conditions (Qi et al, 2013), or measured the stress effects after a much shorter period of treatment Wang et al, 2015). There also may be species-specific differences within the grasses.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Mmentioning
confidence: 99%
“…By using a deep transcriptome sequencing approach, Qi et al (2013) identified 584 lncRNAs in foxtail millet. Among them, 17 lincRNAs and two NATs are drought responsive.…”
Section: Drir Is a Novel Lncrna Regulating Plant Tolerance To Droughtmentioning
confidence: 99%
“…Several reports also show that drought or salt stress could alter lncRNA expression in plants. For example,19,664, and 98 drought-responsive lncRNAs were identified in foxtail millet (Setaria italica), maize (Zea mays), and rice, respectively (Qi et al, 2013;Zhang et al, 2014a;Chung et al, 2016). Salt stress and dehydration stress also alter the accumulation of eight and six lncRNAs, respectively, in Arabidopsis (Arabidopsis thaliana; Ben Amor et al, 2009).…”
mentioning
confidence: 99%
“…A rapid and high throughput screening for drought tolerance during germination in foxtail millet was developed which used polyethylene glycol (PEG-6000) to generate osmotic stress [15]. Multiple methods of gene expression profiling have been employed to identify genes related to drought tolerance in foxtail millet, and these methods identified hundreds of significant changes in expression that corresponded to genes involved in metabolism, proteolysis, and signaling [16][17][18][19]. However, the detailed genetic mechanisms responsible for variation in drought tolerance among foxtail millet lines remain uncharacterized.…”
Section: Setaria As Model For the Panicoideae Crops And C 4 Photosyntmentioning
confidence: 99%